ANALISIS STRUKTUR PASAR KARET PETANI EKS UPP TCSDP DI DESA BUKIT SAKAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Sunarti Sunarti; Ermi Tety; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Agriculture Marketing is a series of economic aktivities consecutive that accur during the course of commodity agricultural products from primary producer to consumer. The purposes of this research are to analyse: market structure farmer Ex UPP TCSDP in Bukit Sakai village Kampar Kiri district of Kampar regency. This research started from June 2015 till March 2016. The research method who used in this research is survey method. The sampling method in this research used purposive sampling with criteria of rubber Ex UPP TCSDP age ranging from 15-30 years. Intake of sample to rubber compiler and factory used snowball sampling method by following its marketing channel. The research result showed there two marketing channel at Ex UPP TCSDP that on marketing channel I from farmer – collector compiler - big compiler Pekanbaru – Pekanbaru factory. That marketing channel II from farmer – collector compiler - big compiler Medan – Medan factory. In the calculation of the concentration ratio of the traders Pekanbaru has a concentration ratio of 32.77% which leads to the concentration oligopsonistic being, the traders Medan its concentration ratio of 53.91% which leads to a low concentration oligopsony. In Pekanbaru collectors market share amounting to 32.77% which leads to oligopsonistic loose, the traders Medan market share of 67.23% which leads to a strict oligopsony. In the Herfindahl index traders in Pekanbaru 0,10 0,45 Medan traders thus leading to oligopsony. Market structure at rubber marketing of Ex UPP TCSDP in Bukit Sakai village imperfectly competitive market leads to oligopsony. Keywords: TCSDP, marketing channel, market structure. Farmer, Agricultur Marketing